Analysis of vitamin E in leprosy patients - Hazlianda, Cut Putri; Dalimunthe, Dina Arwina; Partogi, Donna (Journal of Pakistan Association of Dermatologists, 2023)
Background Mycobacterium leprae is the primary causative agent of the chronic infectious illness leprosy, can affect peripheral nerves and the skin. Vitamin E, a fat-soluble antioxidant, is essential in the body and can modulate various immune responses. Previous study showed reduced vitamin E levels in leprosy patients. This study evaluated vitamin E levels, differences in paucibacillary and multibacillary type leprosy subjects, and the correlation between bacterial index and vitamin E levels. Methods In this study, 24 leprosy subjects have been included in this analytical investigation using a cross-sectional methodology. Between March and October 2018, the study was carried out in the Dermatology and Venerology Department of the Leprosy Division at the Haji Adam Malik General Hospital in Medan, Pirngadi General Hospital in Medan, Belidahan Leprosy Hospital, Sicanang Leprosy Hospital, and Lau Simomo Leprosy Hospital. Results Leprosy was found primarily in males (70.8%), 16–35 years old (50%). The mean value of vitamin E levels in MB leprosy (9.62±3.91 mg/L) was lower than in PB leprosy (10.55±2.12 mg/L). This study showed a statistically significant correlation between bacterial index and vitamin E levels (r=0.284, p=0.043). Conclusion There is a correlation between bacterial index and vitamin E levels.